2013
DOI: 10.1186/1559-0275-10-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of amniocytes reveals potentially dysregulated molecular networks in Down syndrome

Abstract: BackgroundDown syndrome (DS), caused by an extra copy of chromosome 21, affects 1 in 750 live births and is characterized by cognitive impairment and a constellation of congenital defects. Currently, little is known about the molecular pathogenesis and no direct genotype-phenotype relationship has yet been confirmed. Since DS amniocytes are expected to have a distinct biological behaviour compared to normal amniocytes, we hypothesize that relative quantification of proteins produced from trisomy and euploid (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 28 publications
(27 reference statements)
2
28
1
Order By: Relevance
“…Among them, most have focused on T21 because it is the most common aneuploidy worldwide . Cho's research revealed that over 900 proteins were dysregulated in amniocytes with T21, and their most significant finding was the upregulation of Cu, Zn superoxide dismutase and the down regulation of nestin downregulated in amniocytes with T21 . In this study, 2DE and MALDI‐TOF MS were used to identify candidate biomarker proteins in T21 amniocytes, and 6 proteins were found to be upregulated and no significant changes of expressions of Cu, Zn superoxide dismutase or nestin in our study.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Among them, most have focused on T21 because it is the most common aneuploidy worldwide . Cho's research revealed that over 900 proteins were dysregulated in amniocytes with T21, and their most significant finding was the upregulation of Cu, Zn superoxide dismutase and the down regulation of nestin downregulated in amniocytes with T21 . In this study, 2DE and MALDI‐TOF MS were used to identify candidate biomarker proteins in T21 amniocytes, and 6 proteins were found to be upregulated and no significant changes of expressions of Cu, Zn superoxide dismutase or nestin in our study.…”
Section: Discussionsupporting
confidence: 47%
“…10 Cho's research revealed that over 900 proteins were dysregulated in amniocytes with T21, and their most significant finding was the upregulation of Cu, Zn superoxide dismutase and the down regulation of nestin downregulated in amniocytes with T21. 11 In this study, 2DE and MALDI-TOF MS were used to identify candidate biomarker proteins in T21 amniocytes, and 6 proteins were found to be upregu- Calumenin, which is encoded by a gene located in chrome 7 called CALU, is a 48-kDa Ca 2+ -dependent protein. It is a member of Ca2 +binding family, which has Cab45, 12 reticulocalbin, 13 ERC-55, 14 and crocalbin.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewer account details (http://www.ebi.ac.uk/pride/archive/login): Username: ****** Password: ****** Development of SRM assays for the verification phase. SRM assays were developed as previously described 23,44,48,74,76 . Briefly, the Peptide Atlas (www.peptideatlas.org) was used to select top 5-7 peptides (charge +2 and +3) for each of 148 candidate proteins and 11 control proteins (representing other six glands or cell types in the male urogenital system).…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 99%
“…4,5 The most promising biomarkers are also explored for the molecular mechanisms of their differential expression or regulation. [6][7][8] Recent genomic studies on the primary prostate adenocarcinoma revealed major subtypes defined by the gene fusions of E26 transformation-specific (ETS) transcription factors, and mutations in SPOP, FOXA1, and IDH1 genes. 9,10 The most common genomic subtype of primary prostate cancer was represented by the fusion of the androgen-responsive gene TMPRSS2 with the transcription factor ERG (~50% of all cases).…”
Section: Introductionmentioning
confidence: 99%